Survey of Tqm Success Factors In Manufacturing and Service Industries: Exploring the Views and Definitions of TQM (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Over the past fewdecades, quality gurus such as Deming (1986), Juran (Juran and Gryna, 1993),Crosby (1979), Feigenbaum (1991), and Ishikawa (1985), the primary authoritiesof total quality management (TQM), have developed certain propositions in thefield of TQM, which have gained significant acceptance throughout the world. Theirinsights provide a good understanding of the TQM philosophy, principles, andpractices. After careful study of their work, it has been found that thesequality gurus have different views about TQM, although some similarities can befound. Worldwide, there are several Quality Awards such as the Deming Prize(1996) in Japan, the European Quality Award (1994) in Europe, and the MalcolmBaldrige National Quality Award (1999) in the United States of America. Eachaward model is based on a perceived model of TQM. However, the three awardmodels are different from each other and each has its own characteristics. Inthe field of TQM implementation, much research has already been conducted,different researchers adopting different definitions of TQM. The concept isstill a subject of debate (Easton and Jarrell, 1998), still a hazy andambiguous concept (Dean and Bowen, 1994). So far, TQM has come to meandifferent things to different people (Hackman and Wageman, 1995).